The Pengaruh Work Ethic dan Work Motivation terhadap Job Commitment pada Manajemen Kepengurusan Atlet Taekwondo Surabaya - Jalu Aruna Kastara; Khoirur Rozaq (Universitas Negeri Surabaya, 2025)
This study investigates the effect of work motivation and ethics on the job commitment of BPTI Surabaya administrators. The study's population consisted of 159 participants, and the sample comprised 113 individuals. The data collection was accomplished through the use of questionnaires and various documentation methods. Data sources were obtained through both primary and secondary data. Data processing and analysis are performed using SPSS (Statistical Package for the Social Sciences) version 15.0. The research findings indicate that work motivation has a positive and significant effect on the job commitment of administrators. The t-count value (8.637) is greater than the t-table value (2.390), and the p-value of 0.000 is less than 0.05, which supports this. Work ethic has a positive and significant influence on administrators' job dedication, as indicated by the t-count value (4.184), which exceeds the t-table value (2.390), and a p-value of 0.000, which is less than 0.05. There is a positive and substantial impact on management's job commitment when work ethics and work motivation are integrated simultaneously. Work motivation exerts a more significant effect on management's job commitment than work ethic, as indicated by the regression coefficient of the work motivation variable (0.685), which surpasses that of work ethic (0.409). Work motivation (X1) and work ethic (X2) account for 86.00% of the manager's job commitment (Y). Conversely, the remaining 14.00% is affected by extraneous elements or variables beyond the purview of this study, including work morale, atmosphere, workability, education, and training.